Peningkatan Penjualan Melalui Promosi Dengan Sarana Media Sosial Pada Umkm Kain Songket di Desa Limbang Jaya - Setiawan Jhody; Efan Elpanso; Dina Mellita (Jurnal Cakrawala Akademika, 2024)
This research aims to increase the sales of songket fabrics at UMKM in Limbang Jaya Village through promotional strategies using social media. The activities were carried out in the Thematic Real Work Lecture (KKNT) program for 36 days, from October 16 to November 21, 2024. Prior to the implementation of KKNT, the promotion of songket fabrics in this village was still limited to traditional methods such as word-of-mouth promotion. Through training and mentoring, the community of Limbang Jaya Village began to understand and utilize social media, including Facebook, Instagram, and WhatsApp Business, as a means of wider and more effective promotion. The results of the activities show an increased understanding of digital promotion and the potential for market expansion for local songket fabric products. With this approach, the promotion of songket fabrics in Limbang Jaya Village was successfully improved, having a positive impact on efforts to expand the marketing network and encourage the growth of local UMKM.